"Avoid health warnings on all tobacco products for just as long as we can": a history of Australian tobacco industry efforts to avoid, delay and dilute health warnings on cigarettes. (26th November 2003) - Chapman, S; Carter, S M
Abstract : Objective: To review critically the history of Australian tobacco industry efforts to avoid, delay, and dilute pack warnings on cigarettes. Design: Systematic keyword and opportunistic website searches of tobacco industry internal documents made available through the Master Settlement Agreement. Results: Four industry strategies and six recurrent arguments used by the industry are described, which were used to thwart the passage of three generations of health warnings (implemented in 1973, 1987, and 1995). These strategies are shown to have been associated with major delays in the implementation of the warnings and in keeping them inconspicuous, unattributed to the industry and non-specific, and particularly in delaying the use of warnings about addiction. The industry today continues to oppose warnings, which might "repel" smokers from tobacco use. Conclusions: Efforts by governments to introduce potent health warnings will be resisted by the tobacco industry. Tobacco control advocates should anticipate and counter the strategies and arguments used by the industry, which are described in this paper if they wish to maximise the use of the pack as a vehicle for raising awareness about the harms of smoking.